An Arabidopsis protoplast isolation method reduces cytosolic acidification and activation of the chloroplast stress sensor SENSITIVE TO FREEZING 2. (2nd September 2019) - Barnes, Allison C.; Elowsky, Christian G.; Roston, Rebecca L.
ABSTRACT: Chloroplasts adapt to freezing and other abiotic stresses in part by modifying their membranes. One key-remodeling enzyme is SENSITIVE TO FREEZING2 (SFR2). SFR2 is unusual because it does not respond to initial cold stress or cold acclimation, instead it responds during freezing conditions in Arabidopsis. This response has been shown to be sensitive to cytosolic acidification. The unique lipid products of SFR2 have also been detected in response to non-freezing stresses, but what causes SFR2 to respond in these stresses is unknown. Here, we investigate protoplast isolation as a representative of wounding stress. We show that SFR2 oligogalactolipid products accumulate during protoplast isolation. Notably, we show that protoplast cytosol is acidified during isolation. Modification of the buffers reduces oligogalactolipid accumulation, while prolonged incubation in the isolated state increases it. We conclude that SFR2 activation during protoplast isolation correlates with cytosolic acidification, implying that all SFR2 activation may be dependent on cytosolic acidification. We also conclude that protoplasts can be more gently isolated, reducing their stress.